2000
DOI: 10.1523/jneurosci.20-23-08897.2000
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic Reticular Nucleus Activation Reflects Attentional Gating during Classical Conditioning

Abstract: All senses, except olfaction, are routed through the thalamus to cerebral cortex. Thus, the thalamus is often referred to as the sensory gateway to cortex. Located between thalamus and cortex is a thin lamina of neurons called the thalamic reticular nucleus, which may function as an attentional gate. The phenomenon of blocking in classical conditioning provides an opportunity to test whether an attended stimulus activates the thalamic reticular nucleus more than an unattended stimulus: when a second stimulus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(58 citation statements)
references
References 31 publications
1
57
0
Order By: Relevance
“…In monkey and rodent, shifting the animal's attention from one sensory modality to another increased the neuronal activity in the TRN sector associated with the attended stimulus (McAlonan et al 2000(McAlonan et al , 2006. Conversely, during an attentional task involving valid and invalid cues, unilateral TRN lesions abolished the processing advantage conferred by cues contralateral to the lesion (Weese et al 1999).…”
Section: Functional Implicationsmentioning
confidence: 97%
“…In monkey and rodent, shifting the animal's attention from one sensory modality to another increased the neuronal activity in the TRN sector associated with the attended stimulus (McAlonan et al 2000(McAlonan et al , 2006. Conversely, during an attentional task involving valid and invalid cues, unilateral TRN lesions abolished the processing advantage conferred by cues contralateral to the lesion (Weese et al 1999).…”
Section: Functional Implicationsmentioning
confidence: 97%
“…In most sensory systems, the majority of feedback passes through the thalamus, which has been suggested to act as an "attentional gate" (McAlonan et al 2000;Spence et al 2001). Olfactory information, however, does not pass through the thalamus as it projects to higher cortical regions; because of this, some researchers have suggested that attentional processes cannot be applied to olfactory stimuli as to other stimuli (Smythies 1997).…”
Section: Centrifugal Projections In Olfactionmentioning
confidence: 99%
“…Lesions of visual TRN abolished priming effects associated with cues to contralateral visual targets in an attentional orienting task (Weese et al, 1999), demonstrating a link between TRN and the attentional effects of visual cues. Other studies focused on the interactions between the modality-specific sectors of TRN, showing a selective increase in Fos-positive neurons in the sector of TRN associated with the modality of the attended stimulus (Montero, 1997(Montero, , 1999(Montero, , 2000McAlonan et al, 2000). Although these lesion and histological studies provide evidence that modulation of TRN occurs with attention, they could not address whether the changes were increases or decreases of activity or whether the changes occurred fast enough to modulate visual responses in the LGN.…”
Section: Introductionmentioning
confidence: 98%